Sex-related differences of lipid metabolism induced by triptolide: The possible role of the LXRα/SREBP-1 signaling pathway - Zhenzhou eJiang; Zhenzhou eJiang; Xiao eHuang; Shan eHuang; Hongli eGuo; Lu eWang; Xiaojiaoyang eLi; Xin eHuang; Xin eHuang; Tao eWang; Luyong eZhang; Luyong eZhang; et al. (Frontiers Media S.A., 2016)
Triptolide, a diterpenoid isolated from the plant Tripterygium Hook. f., exerts a unique bioactive spectrum of anti-inflammatory and anticancer activities. However, triptolide's clinical applications are limited due to its severe toxicities.Fatty liver toxicity occurs in response to triptolide, and this toxic response significantly differs between males and females. This report investigated the pathogenesis underlying the sex-related differences in the dyslipidosis induced by triptolide in rats. Wistar rats were administered 0, 150, 300 or 450 μg triptolide/kg/day by gavage for 28 days. Ultrastructural examination revealed that more lipid droplets were present in female triptolide-treated rats than in male triptolide-treated rats. Furthermore, liver triglyceride, total bile acid and free fatty acid levels were significantly increased in female rats in the 300 and 450 μg/kg dose groups. The expression of liver X receptor α (LXRα) and its target genes, cholesterol 7α-hydroxylase (CYP7A1) and Sterol regulatory element-binding transcription factor 1(SREBP-1), increased following triptolide treatment in both male and female rats; however, the female rats were more sensitive to triptolide than the male rats. In addition, the expression of acetyl-CoA carboxylase 1(ACC1), a target gene of SREBP-1, increased in the female rats treated with 450 μg triptolide/kg/day, and ACC1 expression contributed to the sex-related differences in the triptolide-induced dysfunction of lipid metabolism. Our results demonstrate that the sex-related differences in LXR/SREBP-1-mediated regulation of gene expression in rats are responsible for the sex-related differences in lipid metabolism induced by triptolide, which likely underlie the sex-related differences in triptolide hepatotoxicity. This study will be important for predicting sex-related effects on the pharmacokinetics and toxicity of triptolide and for improving its safety.